PENGARUH METODE LATIHAN DAN MOTOR EDUCABILITY TERHADAP KETERAMPILAN KARATE-KATA - SITI AISYAH, SA (2020)
ABSTRACT The complexity of karate kata's movements needs a more appropriate training method so that athletes can master it according to the World Karate Federation's rules. Therefore, this study aims to investigate the effect of the whole part whole training method and the whole training method on students with high and low motor abilities towards the karate kata skills of students who joined the karate extracurricular program. This research was conducted using ex post facto method with a 2x2 factorial design. The research sample consisted of 80 people selected from students who joined karate extracurricular program at SDIT Darul Ma'arif Bandung Regency by using simple purposive sampling. The training was carried out twice a week for 20 weeks during the preparation for semester II of the 2019 karate belt examination. Karate Kata Heian Shodan skill was used as the test instrument, and it was assessed by a West Java provincial certified Inkanas referee. Each student practiced the Karate Kata Heian Shodan alone in a match atmosphere. The obtained data were processed with MS Excel 2010 software using a two-way Anova test. The results revealed that: 1). The whole part whole method is better than the whole method for karate kata skills 2). There is no interaction between the training method and motor ability towards karate kata skills. 3). Students with high motor ability trained with the whole part whole method had better karate kata skills than students trained with the whole method 4). Students with high motor educability trained with the whole part whole method were better than students trained with the whole method. This study's implication is that the whole part whole method enables the coach to improve the students' karate kata skills easier. Keywords: whole part whole practice method, whole practice method, motor educability, karate-kata skill